Dhimmi Citizens: Non-Muslims in the New Islamist Discourse. (1st October 2016) - Ovamir Anjum
Abstract : Accounts of modern Islamic reformist currents offered by recent studies take for granted that Islamists have embraced the modern nation-state, and, relatedly, that there is consequently a rupture in Islamic discursive tradition. This article seeks to nuance these notions by examining "the new Islamist" discourse on the poignant question of non-Muslim belonging in an Islamic state. Not all Islamists have embraced the nation-state and its majoritarian and secular logics in quite the same way. Those who remain committed to making ijtihad from within the Islamic tradition, such as Yusuf al-Qaradawi, continue to offer a fundamentally different view of political authority than those republican Islamists, such as Fahmi Huwaydi and Tariq al-Bishri, who treat Islamic tradition as a mine of wisdom and source of republican values and inspiration rather than a coherent system of norm production. This difference can be detected even when they appear to substantially agree on a number of policies and aspirations, such as the accommodation of non-Muslims as not only tolerated but as nearly equal citizens in an Islamic state.